The Role of Personality and Self-Motivation in Political (Dis)Engagement - Meng, Daryl Loh Wei; Berezina, Eliza (UI Scholars Hub, 2020)
Perceived loss of control of ones’ political environment breeds cynicism and lowered self-motivation for future political action, all of which are marked indicators of learned helplessness. This leads to disengagement of a country’s people in political activity, thus leaving the government unaccountable and unregulated, while allowing corruption and selfserving policies to plague the nation’s well-being. Therefore, this study aimed to better understand the associations among political apathy, learned helplessness, age, and personality traits. It was hypothesized that learned helplessness, age, and personality traits would be significant predictors of political apathy. Participants were 200 Malaysian individuals (91 males, 109 females, M = 32.93, SD = 13.91) who completed questionnaires including the MiniInternational Personality Item Pool, Self-Motivation Scale, and Voter Involvement Scale. Learned helplessness and Neuroticism were positively correlated with political apathy, whereas Extraversion and Intellect showed negative correlations with political apathy. Age, Agreeableness, and Conscientiousness showed no significant relationships with political apathy. Extraversion was the most significant predictor of political apathy, followed by intellect. Thus, the insights yielded from this study may allow for its accumulated knowledge to be informedly applied to reach an artificial resurgence in political engagement.